Evolutionary Governance Theory Theory and Applications - Beunen, Raoul; Van Assche, Kristof; Duineveld, Martijn; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume presents empirical studies and theoretical reflections on Evolutionary Governance Theory (EGT), its most important concepts and their interrelations. As a novel theory of governance, EGT understands governance as radically evolutionary, which implies that all elements of governance are subject to evolution, that these elements co-evolve and that many of them are the product of governance itself. Through this book we learn how communities understand themselves and their environment and why they create the complex structures and processes we analyze as governance paths. Authors from different disciplines develop the EGT framework further and apply it to a wide range of governance issues that cover topics such as welfare state governance, networks of power, governance of agricultural resources etc. The contributors also reflect on the possibilities and limitations of steering, intervention, management and development in a world continuously in flux. It bridges the gap between more fundamental and philosophical accounts of the social sciences and applied studies, offering theoretical advancement as well as practical recommendations.
Part I: Introduction -- Part II: Configurations of Actors and Institutions -- Part III: Configurations of Power/Knowledge -- Part IV: Case Studies -- Part V: Conclusions -- Glossary.
Keywords: Economics; Environmental management; Development Economics; Economics/Management Science; Public Administration; Political Science, general; Corporate Governance; Development Economics; Knowledge - Discourse; Environmental Management